Effects of Salicylic Acid on some Growth and Physiological Characteristics of Lettuce (Lactuca sativa L.) under Cadmium Stress Conditions - Talabany, Nazhad Khalid; Albarzinji, Ikbal M. (Science Journal of University of Zakho, 2023)
Lettuce (Lactuca sativa L.) is considered as the most cultivated and consumed leafy vegetable all over the world. In Erbil Governorate, most farmers used sewage water to irrigate lettuce, which caused health risks especially heavy metal pollutants including cadmium. This research was applied as a factorial experiment to investigate the effects of foliar spraying of salicylic acid (SA) (0,0.5,1, 1.5 or 2mM) followed by spraying cadmium chloride (Cd) (0, 1, 2, or 4mM) on the growth, and some physiological and biochemical characteristics of this plant. Results show that most vegetative growth characteristics responded inversely to increasing SA concentrations, whereas the response of root performance improved with using SA application. A low concentration of Cd (1mM) improved root and shoot performance, whereas increasing the concentration to 4 mM decreased these characteristics significantly compared to no Cd added plants, except for the percent of shoot dry matter. Most of photosynthetic pigments decreased significantly by foliar spraying with SA and Cd. Applications of SA increased catalase enzyme activity significantly compared to no SA treated plants. Cadmium foliar application increased peroxidase enzyme activity, ascorbic acid, proline, and percent of total carbohydrate content and decreased catalase enzyme activity and the percent of infection with watery soft rot significantly compared to no Cd treated plants. It is concluded that lettuce tolerance to cadmium stress was increased by pretreatment foliar application of SA.